1711 Prut seferi’ nin lojistik faaliyetleri - Yıldız, Hakan (My University, 2000)
Bu araştırma, Osmanlı İmparatorluğu'nun XVIII. yüzyılın ilk büyük seferi olan Prut Seferi'ne hazırlanmasını konu almaktadır. Araştırmada, sefer için yapylan hazyrlyklaryn, âdeta klâsikle?mi? olan bir sefer yönetim sistemi ile sava? co?rafyasy üzerinde uygulanmasy ortaya konulmaya çaly?ylmy?tyr. Bu sistem, insan gücü seferberli?i, alt yapy faaliyetleri ve ia?e-mühimmat ikmali adlary altyndaki üç ana lojistik organizasyondan meydana gelen bir koordinasyon bünyesinde ele alynmy?tyr. Giri? bölümünde, Rusya'nyn sycak denizlere inme politikasynyn ilk ciddî te?ebbüsleri ve Osmanly Ymparatorlu?u'nu parçalamak için hristiyan tebaya yapylan din propagandalarynyn ilk plânly uygulamalaryna de?inilmi? ve Prut Seferi'nin sebepleri ve sonuçlary itibaryyla Avrupa ile Dünya tarihinin dönüm noktalaryndan biri oldu?u izah edilmeye çaly?ylmy?tyr. Birinci Bölümde, sefer için insan gücü seferberli?i ve silâhly kuvvetler ile geri hizmet gruplarynyn lojistik faaliyetlere yapty?y katkylar anlatylmy?tyr. Ykinci Bölümde, lojistik ikmalin en hyzly ve kesintisiz yapylabilmesi için ula?ym sisteminin iyile?tirilmesi ile ilgili alt yapy faaliyetleri ele alynmy?tyr. Üçüncü Bölümde ise, sefer için imparatorlu?un çe?itli yerlerinden ia?e, silâh ve mühimmat temin edilmesi ve bunlaryn harekât hâlindeki orduya sevkyyaty incelenmi?tir.

The subject of this research is the preparations made for the Prut Campaign, the first big campaign of the Ottoman Empire in the 18th century. In the research, the practice on the battle geography of preparations made for the campaign have been tried to be given with a 'campaign administration system' that has virtually become classic. This system has been taken up under the structure of a coordination formed of tree main logistic organizations named as 'mobilization of manpower', 'infrastructure activities' and 'supply of feedings and munitions'. In the Introduction, the first attemps of Russia's policy to reach warm waters and the first planned practices of religious propaganda against the Christian subjects to destroy the Ottoman Empire have been referred to, and the fact that the Prut Campaign was one of the turning points of the European and the World History with respect to its causes and outcomes has been tried to be explained. In the 'First Section', mobilization of manpower for the campaign, and the contributions made by the armed forces and supply services behind the front to the logistic activities have been explained. In the 'Second Section', infrastructure activities relating to the betterment of transportation system to enable a quick and non-stop supply have been explained. And in the 'Third Sections', supply of arms and munitions from various parts of the Empire and their dispatch to the Army-in-campaign have been studied.
Keywords: Osmanlı İmparatorluğu_Gerileme ve çöküş dönemi, 1683-1922; Prut Savaşı, 1711; SAVAŞ_TARİH